Strategic Navigation of Waqf Law: Maximizing the Productivity of Waqf Land Management - Shahrullah, Rina Shahriyani; Syarief, Elza; Arifin, Inal (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Waqf is considered a recommended act of worship in Islamic teachings and reflects the devotion of individuals. To safeguard the community's interests, the state has established a legal framework concerning Waqf through Law Number 41 of 2004. According to this law, waqf pledges are no longer limited to verbal declarations but must be recorded in written form through an official waqf pledge deed. Furthermore, the law emphasizes the need for productive waqf management. In East Tanjungpinang District of Tanjungpinang City, the quantity and size of waqf land surpass those of other districts within the city. This presents an intriguing opportunity to investigate the effectiveness of productive waqf land management in this District based on Law No. 41 of 2004 on Waqf. The research takes an empirical juridical approach, aiming to assess effectiveness and identify constraints encountered in the implementation of the Waqf Law in East Tanjungpinang District. Data for the study was collected from various sources, including books, journals, relevant documents (secondary data), and interviews conducted with stakeholders involved in waqf management (primary data). The findings of the study demonstrate that waqf implementation in East Tanjungpinang District aligns with Islamic teachings and Law No. 41 of 2004 concerning Waqf. However, several obstacles hinder its effective implementation, including law enforcement, infrastructure, community, and cultural factors.